2014
DOI: 10.1089/ars.2013.5486
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen and Nitrogen Species in Steatotic Hepatocytes: A Molecular Perspective on the Pathophysiology of Ischemia-Reperfusion Injury in the Fatty Liver

Abstract: Significance: Hepatic ischemia-reperfusion (IR) injury results from the temporary deprivation of hepatic blood supply and is a common side effect of major liver surgery (i.e., transplantation or resection). IR injury, which in most severe cases culminates in acute liver failure, is particularly pronounced in livers that are affected by nonalcoholic fatty liver disease (NAFLD). In NAFLD, fat-laden hepatocytes are damaged by chronic oxidative/ nitrosative stress (ONS), a state that is acutely exacerbated during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 236 publications
(282 reference statements)
4
89
1
3
Order By: Relevance
“…In this study, we indeed found increased ROS overproduction and oxidative stress in 10% fructose-fed rat livers and 5 mM fructose-exposed cultured hepatocytes, partly mediated by inhibition of Nrf2 transcriptional activity and the ROS-TXNIP signaling axis. Recently, more evidence demonstrates the importance of fructose in steatotic hepatocytes (43). These contradictory findings may be related to fructose concentration, its metabolism, and use of different experimental models.…”
Section: Figmentioning
confidence: 99%
“…In this study, we indeed found increased ROS overproduction and oxidative stress in 10% fructose-fed rat livers and 5 mM fructose-exposed cultured hepatocytes, partly mediated by inhibition of Nrf2 transcriptional activity and the ROS-TXNIP signaling axis. Recently, more evidence demonstrates the importance of fructose in steatotic hepatocytes (43). These contradictory findings may be related to fructose concentration, its metabolism, and use of different experimental models.…”
Section: Figmentioning
confidence: 99%
“…The mechanisms described under Ischemia and Mitochondrial Metabolites illustrate the pathways of ROS formation during hepatic I/R, which can compromise liver function during reperfusion by oxidizing proteins (33). Oxidative modification of amino acids in mitochondrial complex I, III and V has been observed in mouse livers subjected to I/R, leading to decreased ATP production during early reperfusion (34).…”
Section: Hypothermia and Immunomodulationmentioning
confidence: 99%
“…When ATP stores drop below these limits through the aforementioned mechanisms, the apoptotic process is redirected toward inactivation of hepatic insulin receptors by JNK (57). As stated in Hypothermia and Immunomodulation, JNK is activated by TNF-α and ROS during hepatic I/R injury (58), after which JNK initiates a positive feedback loop that enhances its own activation by upholding TNF-α and ROS formation (33). Both TNF-α and ROS, however, can also induce hepatocyte insulin resistance independently of JNK (57).…”
Section: Hypothermia and Immunomodulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravascular sources of superoxide during I/R include xanthine oxidase and NADPH oxidase (NOX) in endothelial cells, leukocytes, and platelets [10], whereby NOX1 [26], NOX2 [27], and NOX4 [28] have been implicated in renal I/R. Although relatively innocuous itself, superoxide gives rise to more toxic secondary and tertiary reactive intermediates [29] that form from the superoxide dismutase-catalyzed end product hydrogen peroxide [30][31][32]. Superoxide also reacts with NO that is extensively produced during renal I/R [33] to form peroxynitrite [34,35], which oxidatively modifies proteins, DNA bases, and lipids by nitration, rendering the biomolecules dysfunctional.…”
Section: Introductionmentioning
confidence: 99%